2016
DOI: 10.1177/0044118x13513479
|View full text |Cite
|
Sign up to set email alerts
|

Sport Involvement and Educational Outcomes of High School Students

Abstract: This study examined the relations among sport involvement and social and personal influences on high school students' educational expectations and attainment, using National Education Longitudinal Survey-88. Athletic engagement, educational expectations of significant others, peer support for academics, parental involvement in academics, and academic and athletic identities were measured in the 10th grade. Educational expectations and attainment were measured in the 12th grade and 8 years after high school. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Early research using data collected from day-students in the USA showed that over 15 years, extracurricular activities could have positive effects on aspiration and attainment (Otto, 1975;Otto & Alwin, 1977). This literature has progressed through using a range of methods to show that different forms of activity influence identity formation and lead to both positive and negative academic and social outcomes, which depend on student backgrounds and the context of the activities (Barber, Eccles & Stone, 2001;Eccles & Barber, 1999;Farb & Matjasko, 2012;Hwang, Feltz, Kietzmann & Diemer, 2016;Marsh & Kleitman, 2002). That sport and extracurricular activities in mainstream schooling enter our review of literature is an indicator that there is a shortage of published research on outdoor education programmes at boarding schools --whether longitudinal or not, and irrespective of methodologies employed.…”
Section: Long Term Influences Of Boarding Schoolsmentioning
confidence: 99%
“…Early research using data collected from day-students in the USA showed that over 15 years, extracurricular activities could have positive effects on aspiration and attainment (Otto, 1975;Otto & Alwin, 1977). This literature has progressed through using a range of methods to show that different forms of activity influence identity formation and lead to both positive and negative academic and social outcomes, which depend on student backgrounds and the context of the activities (Barber, Eccles & Stone, 2001;Eccles & Barber, 1999;Farb & Matjasko, 2012;Hwang, Feltz, Kietzmann & Diemer, 2016;Marsh & Kleitman, 2002). That sport and extracurricular activities in mainstream schooling enter our review of literature is an indicator that there is a shortage of published research on outdoor education programmes at boarding schools --whether longitudinal or not, and irrespective of methodologies employed.…”
Section: Long Term Influences Of Boarding Schoolsmentioning
confidence: 99%
“…The results of the present study also indicated that structure-related complications, including those that are undesirable in the course of development of extra-curricular courses. Hwang, Feltz, Kietzmann & Diemer (2016) pointed out that the lack of proper structure in the path of school sport development was one of the problems in this area. With this in mind, it can be stated that the results of the present study are in line with the results of Huang, Feltz, Kitzman, and Dimer (2016).…”
Section: Discussionmentioning
confidence: 99%
“…classmates; Bandura, 1986). In addition, according to the expectancy-value theory (Eccles & Wigfield, 2002), peer influence and expectations have significant impacts on junior school students' participation in sports activities (Hwang, Feltz, Kietzmann, & Diemer, 2013). Role models can influence individual behavior through values reinforcement (Fredricks & Eccles, 2002).…”
Section: The Association Between Parental Ses Classmate Support Anmentioning
confidence: 99%